Trigeminal Neuralgia — A Debilitating Facial Pain - McMillan, Roddy (Rev Pain, 2011)
Trigeminal neuralgia (TN) is characterised by sudden usually unilateral severe, brief, stabbing, recurrent episodes of pain in the distribution of one or more branches of the trigeminal nerve. Diagnosis is largely based on clinical history due to the current lack of objective investigations. MRI can identify those patients who have TN secondary to an underlying pathology such as multiple sclerosis. The first line medical management remains carbamazepine, with oxcarbazepine being the second choice medication. Both percutaneous techniques targeting the Gasserian ganglion and microvascular decompression can be considered effective in the management of TN. Microvascular decompression is considered to provide on average, the longest pain free period post surgery. There are a number of TN associations and support groups which provide a valued service to patients and clinicians. Due to a dearth of high quality studies in many aspects of the condition, TN requires further research to be conducted.